2021
DOI: 10.1108/jmtm-12-2020-0467
|View full text |Cite
|
Sign up to set email alerts
|

Being lean: how to shape digital transformation in the manufacturing sector

Abstract: PurposeIndustry 4.0 and Lean Production are a successful match in terms of performance improvement. While we understand the combined potential, there is still poor understanding of how companies should embrace digital transformation to make it successful and sustainable, and the role that lean plays in it. In this paper, we investigate how manufacturing companies embark upon digital transformation and how being lean might affect it.Design/methodology/approachWe conducted multiple case studies with 19 manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 71 publications
2
48
0
Order By: Relevance
“…group she participated in for the board of directors in a foreign language, something she would not have dreamt of doing before participating in the action learning intervention. Rossini et al (2021) suggest that manufacturers should approach lean to achieve a faster and more robust digital transformation, this paper supports a perspective. But how do managers approach lean for undergoing a digital transformation?…”
Section: The Outcome Of the Action Learning Interventionsupporting
confidence: 58%
See 3 more Smart Citations
“…group she participated in for the board of directors in a foreign language, something she would not have dreamt of doing before participating in the action learning intervention. Rossini et al (2021) suggest that manufacturers should approach lean to achieve a faster and more robust digital transformation, this paper supports a perspective. But how do managers approach lean for undergoing a digital transformation?…”
Section: The Outcome Of the Action Learning Interventionsupporting
confidence: 58%
“…Prior research has demonstrated complementarity between I4.0 and lean leading to improved performance and acceleration of a digital transformation (e.g. Buer et al, 2021;Raji et al, 2021;Rossini et al, 2021). But what facilitates this complementarity between I4.0 and lean?…”
Section: Insert Table III 7 Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are increasingly implemented in unison [53,54,63,69]. Digitalization and optimization build on and enhance one another [39,42,47,65,70,71,72,73]. Their combined impact is greater than the sum of the individuals [47,68,72,74].…”
Section: Combination and Benefitsmentioning
confidence: 99%